Social Media and Coronavirus: Paranoid-Schizoid Technology and Pandemic? - Johanssen, Jacob (Hu Arenas, 2020)
This article draws on the psychoanalyst Melanie Klein’s ‘paranoid-schizoid position’ to discuss some exemplary social media posts about the coronavirus. I argue that posts often express experiences, thoughts, and fantasies in a schematic manner. They reproduce a paranoid-schizoid logic by which particular views on the current crisis are articulated and different ones are negated. The Kleinian framework is supplemented with Lacan’s notion of the Discourse of the Hysteric. I argue that the examples discussed in this article are instances of hysteric modes of relating to an Other (e.g. the expert) that is allegedly withholding important information from the subject. Splitting is amplified by the technological functioning of social media themselves which split users along a paranoid-schizoid dynamic for purposes of surveillance, advertising and profit maximization. I conclude by outlining steps towards the Kleinian ‘depressive position’ both in relation to how we engage with COVID-19 and social media. The depressive position acknowledges both good and bad aspects of a given situation. I further show how it can be supplemented via the Lacanian Discourse of the Analyst which includes a commitment to the limits of knowledge, certainty, and prediction.